Promotion of Cell Cycle Arrest and Inhibition of Anchorage-independent Growth of Cervical Cancer HeLa Cells by Ethanol Extract of Croton kongensis - Loan, Nguyen Thi Bich; Thanh, Nguyen Lai; Duez, Pierre; Thang, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
Extracts from Croton kongensis (C. kongensis) exhibit anticancer activities on various cancers. However, there is no research conducted to investigate the effects of C. kongensis extracts on cervical cancer as well as on zebrafish. In this study, we demonstrated that C. kongensis ethanol extract expressed high toxicity to cervical cancer HeLa cells with an IC50 dose of 20.4 µg/mL and to zebrafish embryos with malformations, lethality and hatching inhibition at 72-hpf at the effective dose of 125 µg/mL. Interestingly, treatment with C. kongensis ethanol extract caused cell cycle arrest at the G2 phase. Particularly, percentages of C. kongensis ethanol extract-treated cells in G1, S, G2/M were 70%, 6% and 23%, while percentages of control cells in G1, S, G2/M were 65%, 15% and 18%, respectively. Consistent with cell cycle arrest, the expressions of CDKN1A , CDNK2A and p53 in C. kongensis ethanol extract-treated cells were up-regulated 2.0-, 1.65- and 1.8-fold, respectively. Significantly, treatment with C. kongensis ethanol extract inhibited anchorage-independent growth of HeLa cells; the number of colonies formed in soft-agar of C. kongensis ethanol extract-treated cells was only one-fourth of that of control cells. Overall, we suggest that C. kongensis ethanol extract should be used as a traditional medicine for treatment of cervical cancer.